2023
DOI: 10.3390/healthcare11040562
|View full text |Cite
|
Sign up to set email alerts
|

Study of Burden in Polycystic Ovary Syndrome at Global, Regional, and National Levels from 1990 to 2019

Abstract: Increasing attention has recently been paid to the harm of polycystic ovary syndrome (PCOS) to women. However, due to the inconsistency of global clinical diagnostic standards and the differing allocation of medical resources among different regions, there is a lack of comprehensive estimation of the global incidence and disability-adjusted life years (DALYs) of PCOS. Thus, it is difficult to assess the disease burden. We extracted PCOS disease data from 1990 to 2019 from the Global Burden of Disease Study (GB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Although several previous studies have reviewed the burden of PCOS in multiple regions and countries (Gao et al, 2023;Liu et al, 2021;Sa ri et al, 2022), there are some shortcomings. For example, disability adjusted life years (DALYs) are reported, rather than years lived with disability (YLDs).…”
Section: Introductionmentioning
confidence: 99%
“…Although several previous studies have reviewed the burden of PCOS in multiple regions and countries (Gao et al, 2023;Liu et al, 2021;Sa ri et al, 2022), there are some shortcomings. For example, disability adjusted life years (DALYs) are reported, rather than years lived with disability (YLDs).…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of this disease was reported to be 5.6-8% in Europe [8]. According to recent studies, the prevalence of PCOS in Malaysia is 36.23%, based on the Rotterdam criteria, and 6.8%, based on the National Institute of Health (NIH) [9]. It has been shown that the cause of infertility is failure to ovulate in approximately 75% of cases [8].…”
Section: Introductionmentioning
confidence: 99%